Ответ:
Пошаговое объяснение:
![image](https://tex.z-dn.net/?f=2%29%20y%3D%282%2Fx-6%5Csqrt%7Bx%2Bx%2F4%2B3%7D%20%29%27%3D%282x%5E%7B-1%7D-6%20%28x%2Bx%2F4%2B3%29%5E%5Cfrac%7B1%7D%7B2%7D%20%29%27%3D-2x%5E%7B-2%7D%20-3%20%28x%2Bx%2F4%2B3%29%5E%5Cfrac%7B-1%7D%7B2%7D%20%3D-%5Cfrac%7B2%7D%7Bx%5E%7B2%7D%20%7D%20-%5Cfrac%7B3%7D%7B%5Csqrt%7Bx%2Bx%2F4%2B3%7D%20%7D%20%3C%2Fp%3E%3Cp%3E6%29y%3D%20%28%284x%5E2-1%29%5E4%29%27%3D4%284x%5E2-1%29%5E3)
6)y= ((4x^2-1)^4)'=4(4x^2-1)^3" alt="2) y=(2/x-6\sqrt{x+x/4+3} )'=(2x^{-1}-6 (x+x/4+3)^\frac{1}{2} )'=-2x^{-2} -3 (x+x/4+3)^\frac{-1}{2} =-\frac{2}{x^{2} } -\frac{3}{\sqrt{x+x/4+3} }
6)y= ((4x^2-1)^4)'=4(4x^2-1)^3" align="absmiddle" class="latex-formula">